2001
DOI: 10.1034/j.1399-0004.2001.600607.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of the NOG gene in individuals with proximal symphalangism and multiple synostosis syndrome

Abstract: Proximal symphalangism is an autosomal-dominant disorder with ankylosis of the proximal interphalangeal joints, carpal and tarsal bone fusion, and conductive deafness. These symptoms are shared by another disorder of joint morphogenesis, multiple synostoses syndrome. Recently, it was reported that both disorders were caused by heterozygous mutations of the human noggin gene (NOG). To date, seven mutations of NOG have been identified from unrelated families affected with joint morphogenesis. To characterize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 7 publications
7
66
0
Order By: Relevance
“…[25][26][27][28][29] Two previously reported 17q22 microdeletion, patients were intellectually disabled. 7,8 All patients in our study, including patient 6, have intellectual disability and deletions of NOG and C17ORF67.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28][29] Two previously reported 17q22 microdeletion, patients were intellectually disabled. 7,8 All patients in our study, including patient 6, have intellectual disability and deletions of NOG and C17ORF67.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple synostosis syndrome is also autosomal dominant and is characterized by progressive multiple joint ankylosis and fusion which involves the phalanges, carpal and tarsal bones, as well as the spine [15]. It has been shown that these two disorders in humans are often the result of a mutation in the Noggin gene [8,16,19,30]. This evidence suggests that Noggin, may not only be necessary to limit BMP action in development, but also may be necessary for the maintenance of joint space into adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…These syndromes were shown to be caused by mutations in the BMP antagonist NOG-GIN (NOG; Gong et al, 1999;Dixon et al, 2001;Takahashi et al, 2001;Brown et al, 2002) indicating that inhibition of BMP signaling is pivotal for the process of joint formation. Corroborating this, disruption of the mouse Noggin gene results in enlarged condensations and joint fusions (Brunet et al, 1998).…”
Section: Segmentation Of the Digitsmentioning
confidence: 99%